Formulation of Miconazole-Loaded Chitosan–Carbopol Vesicular Gel: Optimization to In Vitro Characterization, Irritation, and Antifungal Assessment - Syed Sarim Imam; Sadaf Jamal Gilani; Ameeduzzafar Zafar; May Nasser Bin Jumah; Sultan Alshehri (Pharmaceutics, 2023)
Miconazole nitrate (MN) is a poorly water-soluble and antifungal drug used for fungal infections. The present research work was designed to develop topical MN-loaded bilosomes (BSs) for the improvement of therapeutic efficacy. MZBSs were prepared by using the thin-film hydration method and further optimized by using the Box–Behnken statistical design (BBD). The optimized miconazole bilosome (MZBSo) showed nano-sized vesicles, a low polydispersity index, a high entrapment efficiency, and zeta potential. Further, MZBSo was incorporated into the gel using carbopol 934P and chitosan polymers. The selected miconazole bilosome gel (MZBSoG2) demonstrated an acceptable pH (6.4 ± 0.1), viscosity (1856 ± 21 cP), and spreadability (6.6 ± 0.2 cm2). Compared to MZBSo (86.76 ± 3.7%), MZBSoG2 showed a significantly (p < 0.05) slower drug release (58.54 ± 4.1%). MZBSoG2 was found to be a non-irritant because it achieved a score of zero (standard score) in the HET-CAM test. It also exhibited significant antifungal activity compared to pure MZ against Candida albicans and Aspergillus niger. The stability study results showed no significant changes after stability testing under accelerated conditions. MZ-loaded gels could serve as effective alternative carriers for improving therapeutic efficacy.